Death Penalty Disposition in China: What Matters? - Li, Yudu (International journal of offender therapy and comparative criminology, 2018)
In theory, sentencing decisions should be driven by legal factors, not extra-legal factors. However, some empirical research on the death penalty in the United States shows significant relationships between offender and victim characteristics and death sentence decisions. Despite the fact that China frequently imposes death sentences, few studies have examined these sanctions to see if similar correlations occur in China’s capital cases. Using data from published court cases in China involving three violent crimes—homicide, robbery, and intentional assault—this study examines the net impact of offender’s gender, race, and victim-offender relationship on death sentence decisions in China. Our overall multiple regression results indicate that, after controlling for other legal and extra-legal variables, an offender’s gender, race, and victim-offender relationship did not produce similar results in China when compared with those in the United States. In contrast, it is the legal factors that played the most significant role in influencing the death penalty decisions. The article concludes with explanations and speculations on the unique social, cultural, and legal conditions in China that may have contributed to these correlations.